PROSES KEPERAWATAN: TAHAP INTERVENSI DALAM UPAYA PENCEGAHAN KOMPLIKASI PADA PASIEN HIPERTENSI - Nurfadhilah, Naila; Salma, Nisrina Nabila; Maliha, Alya Rafeyfa; Rifqi, Tiara; Puspita, Reva Sri; Ridwan, Heri (SEKOLAH TINGGI ILMU KESEHATAN INDRAMAYU, 2025)
Hypertension is a chronic non-communicable disease with an increasing global and national prevalence. It is often referred to as a silent killer because it typically shows no symptoms until complications arise. Preventing complications in hypertensive patients can be achieved through nursing interventions that are not only procedural but also foster awareness, motivation, and active patient involvement. However, the effectiveness of such interventions in changing patient behavior remains relatively low. This study aims to examine the nursing intervention process as an effort to prevent complications in patients with hypertension. This research used a literature review design with data collected from Google Scholar, PubMed, and Semantic Scholar. The keywords used were “Hypertension,” “Complication prevention,” and “Nursing intervention.” Article selection was guided by the PRISMA framework and included articles written in English or Indonesian, relevant to the topic, full-text, open-access, and published within the last five years. The findings identified five main categories of nursing interventions: education and lifestyle modification, physical activity, non-pharmacological relaxation therapy, complementary therapies such as herbal remedies and acupuncture, and regular monitoring and evaluation. Comprehensive and integrated interventions have been shown to improve patient knowledge, adherence, and quality of life, while also reducing the risk of complications. Conclusion: Holistic nursing interventions play a critical role in preventing hypertension-related complications. Nurses hold a strategic position in designing and implementing effective interventions to improve patient health outcomes.